2014
DOI: 10.2981/wlb.13005
|View full text |Cite
|
Sign up to set email alerts
|

Spatially‐explicit land use effects on nesting of Atlantic Flyway resident Canada geese in New Jersey

Abstract: Atlantic Flyway resident population (AFRP) Canada geese Branta canadensis in New Jersey, USA, have grown dramatically during the last thirty years and are considered as overabundant in many areas. Development of corporate parks and urban areas with manicured lawns and artificial ponds offer ideal nesting habitat for AFRP geese, with limited pressure from hunting or natural predators. As a result, spatial heterogeneity in reproduction must be taken into account in managing the population. We identified the site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 23 publications
(28 reference statements)
0
18
0
Order By: Relevance
“…Early growth was likely due to a combination of factors, including a lack of hunting pressure in urban areas (Smith et al 1999, Atlantic Flyway Council 2011 and a hunting season closure (1995)(1996)(1997)(1998) or other limits on regular hunting season regulations in response to a dramatic decrease in Canada goose in the AFRP during the 1990s (Hindman et al 2004). Population growth of resident Canada goose slowed during the early 2000s, and abundance has since seen a considerable decrease from roughly 104,000 to 77,000 birds during 2006-2014(Nichols and Jones 2015. Heterogeneity in the spatial distribution of population control actions paired with changing land use across the state has provided a complex narrative of habitat-animal relationships over this time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early growth was likely due to a combination of factors, including a lack of hunting pressure in urban areas (Smith et al 1999, Atlantic Flyway Council 2011 and a hunting season closure (1995)(1996)(1997)(1998) or other limits on regular hunting season regulations in response to a dramatic decrease in Canada goose in the AFRP during the 1990s (Hindman et al 2004). Population growth of resident Canada goose slowed during the early 2000s, and abundance has since seen a considerable decrease from roughly 104,000 to 77,000 birds during 2006-2014(Nichols and Jones 2015. Heterogeneity in the spatial distribution of population control actions paired with changing land use across the state has provided a complex narrative of habitat-animal relationships over this time.…”
Section: Discussionmentioning
confidence: 99%
“…Less urbanized land uses (e.g., agricultural and natural lands) were most closely related to the success of a nest at a larger scale of 2.25 km. Our paper expands upon previous work of Guerena et al (2014) by evaluating the influence of land use and weather factors on nest survival, clutch size, and hatchability across 3 decades.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Conversely, non-golfers expressed the exact opposite opinion, with 64% responding negatively due to perceived destruction of habitat [5]. Since that study's publication, however, extensive research has demonstrated the ecological benefits of golf courses, especially in urban settings [16,17,25,26,[28][29][30].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides generalized linear models [20,[43][44][45], several other analytical approaches have been used recently for 'multiscale' analysis: principal coordinates of neighbor matrices [46], multi-scale pattern analysis [47], Spearman's rank correlation [48][49][50][51], multidimensional scaling [52], and classification tree analysis [53]. Analytical approaches from other disciplines have also been borrowed for the identification of relevant analytical foci, such as geostatistical variograms [54].…”
Section: Multi-scale Studies To Find Appropriate Spatial Focusmentioning
confidence: 99%